(untitled) (Circe de clásicos y modernos, 2018)
This article deals with Richard Strauss’s opera production based on mythological and mythical characters. Namely, we focus on the analysis of both of his well known operas, Salomé and Elektra, as innovative pieces of art which foreboded atonality, the greatest musical innovation of the XXth Century. We also review Strauss’s former opera production, characterized by a Wagnerian influence (Guntram, Feuersnot), and his later works, more in the line of the tonal austrogermanic musical tradition, with characters of Greek mythology (Ariadne, Helena, Daphne and Danae) and of the oriental tradition (The woman without a shadow).